"I feel I have no voice": hospital doctors' workplace silence in Ireland. Issue 9 (7th May 2021) - Creese, Jennifer; Byrne, John-Paul; Matthews, Anne; McDermott, Aoife M.; Conway, Edel; Humphries, Niamh
Abstract : Purpose: Workplace silence impedes productivity, job satisfaction and retention, key issues for the hospital workforce worldwide. It can have a negative effect on patient outcomes and safety and human resources in healthcare organisations. This study aims to examine factors that influence workplace silence among hospital doctors in Ireland. Design/methodology/approach: A national, cross-sectional, online survey of hospital doctors in Ireland was conducted in October–November 2019; 1, 070 hospital doctors responded. This paper focuses on responses to the question "If you had concerns about your working conditions, would you raise them?". In total, 227 hospital doctor respondents (25%) stated that they would not raise concerns about their working conditions. Qualitative thematic analysis was carried out on free-text responses to explore why these doctors choose to opt for silence regarding their working conditions. Findings: Reputational risk, lack of energy and time, a perceived inability to effect change and cultural norms all discourage doctors from raising concerns about working conditions. Apathy arose as change to working conditions was perceived as highly unlikely. In turn, this had scope to lead to neglect and exit. Voice was seen as risky for some respondents, who feared that complaining could damage their career prospects and workplace relationships. Originality/value: This study highlights the systemic, cultural and practical issues that pressure hospital doctors in Ireland to opt for silence around working conditions. It adds to the literature on workplace silence and voice within the medical profession and provides a framework for comparative analysis of doctors' silence and voice in other settings.